Thin‐Film Photovoltaics: Combinatorial Investigation and Modelling of MoO3 Hole‐Selective Contact in TiO2|Co3O4|MoO3 All‐Oxide Solar Cells (Adv. Mater. Interfaces 1/2016). Issue 1 (January 2016) - Majhi, Koushik; Bertoluzzi, Luca; Rietwyk, Kevin James; Ginsburg, Adam; Keller, David A.; Lopez‐Varo, Pilar; Anderson, Assaf Y.; Bisquert, Juan; Zaban, Arie
Abstract : In article number 1500405, A. Zaban and co‐workers show the effectiveness of a MoO3 buffer/hole‐contact layer for improving the performance of Co3 O4 |TiO2 all‐oxide hetero‐junction solar cells. The performance is found to be restricted by a poor interface with Au back contacts arising from surface recombination at the Au|Co3 O4 interface. This detrimental effect can be overcome via the introduction of a thin layer of MoO3 between Au and Co3 O4 layers.